LMNA mutation leads to cardiac sodium channel dysfunction in the Emery-Dreifuss muscular dystrophy patient - Perepelina, Kseniya; Zaytseva, Anastasia; Khudiakov, Aleksandr; Neganova, Irina; Vasichkina, Elena; Malashicheva, Anna; Kostareva, Anna (Frontiers in Cardiovascular Medicine, 2022)
Pathogenic variants in the LMNA gene are known to cause laminopathies, a broad range of disorders with different clinical phenotypes. LMNA genetic variants lead to tissue-specific pathologies affecting various tissues and organs. Common manifestations of laminopathies include cardiovascular system abnormalities, in particular, cardiomyopathies and conduction disorders. In the present study, we used induced pluripotent stem cells from a patient carrying LMNA p.R249Q genetic variant to create an in vitro cardiac model of laminopathy. Induced pluripotent stem cell-derived cardiomyocytes with LMNA p.R249Q genetic variant showed a decreased sodium current density and an impaired sodium current kinetics alongside with changes in transcription levels of cardiac-specific genes. Thus, we obtained compelling in vitro evidence of an association between LMNA p.R249Q genetic variant and cardiac-related abnormalities.